Qualitative and quantitative lymphoscintigraphy in the evaluation of lower limbs lymphedema - Dalia,Roberta Maria (2005)
The purpose of this study was to prove the efficiency of qualitative and quantitative lymphoscintigraphy in the diagnosis of the lower extremity lymphedema. Seventy-seven patients had been studied, most of then (85.7%) were female. Patients ages ranged from 18 to 82 years. All patients underwent a bilateral lymphoscintigraphy. Images were recorded with a dual-detector instrument in the whole-body scanning mode. Feet and inguinal static views were acquired within 15 minutes and three hours after radiopharmaceutical injection. Two nuclear doctors evaluated the lymphoscintigrams qualitatively. Quantitative studies of the radiopharmaceutical absorption and the lymph node chain uptake were also obtained. Of the 154 evaluated members, 21.44% (n = 33) were classified as normal, 61.68% (n = 95) as mildly altered and 16.88% (n = 26) much altered. Quantitation of lymphatic chain uptake may be a more sensitive approach to the diagnosis of lymphatic impairment than the qualitative analysis.